ETIKA AUDITOR SEBAGAI PEMODERASI PENGARUH KOMPETENSI DAN INDEPENDENSI PADA KUALITAS AUDIT DI KOTA DENPASAR - Darayasa, I Made; Wisadha, I Gede Supartha (E-Jurnal Akuntansi, 2016)
Audit quality is every possibility that the auditor will find and report violations of the accounting system based on the auditing standards that have been set. This study aims to determine the ethical auditor as a moderating influence on the competence and independence of audit quality in the city of Denpasar. Data collection method used is using questionnaires distributed directly to the auditor who works in Denpasar. The population in this study were all auditors working in the office of the Public Accountant in Denpasar with the overall number of auditors as many as 81 people. The samples used by 65 auditor with purposive sampling method. The analysis technique used is Moderated Regression Analysis (MRA). Based on the analysis and hypothesis testing, it is concluded that (1) the competence of a positive effect on audit quality, (2) the independence of the positive effect on the quality of the audit, (3) the ethics of auditors moderate (strengthen) the effect on audit quality competence, (4) ethics auditor moderate (strengthen) the effect on the independence of audit quality.
Keywords: quality audit, the auditor ethics, competence, independence